WEAR: Wearable technologists engage with artists for responsible innovation: Processes and progress. Issue 1 (1st June 2018) - Baker, Camille; Ranaivoson, Heritiana; Greinke, Berit; Bryan-Kinns, Nick
Wearable technologies are a nascent market, growing exponentially and moving into our everyday lives more and more. They are exciting in their capacity to break down barriers between artists and designers and digital technology companies. Technology is becoming more efficient, accurate, and personalized. Hardware is becoming smaller, less visible, more connected and the collected data more seamless and ubiquitous. At the core of the wearable technology concerns is the amount of data that electronics companies are allowed to collect, in particular of their users' personal data. Numerous technology companies and start-ups are working to make the next wearable device or application for body data tracking. This article provides a first critical analysis of the selection and monitoring processes used in these Open Calls and reports on initial work of the WEAR Sustain network, which for eighteen months has operated as a Pan-European catalyst for 46 projects in wearable technology design and development to the point of market and investment readiness, and discussing next steps for its Sustainability Toolkit for lasting impact.